New thermal packaging with a boiling-driven heat spreader for thermal management of the power electronics - Lim, Hyunmuk; You, Seung M.; Lee, Jungho (Applied Thermal Engineering, 2023)
A new thermal management device with a two-phase flat heat spreader was designed, fabricated, and characterized. The boiling-driven heat spreader (280 mm × 65 mm × 4 mm) is embedded at the thermal packaging air-cooling heat sink for the power electronics. A sintered microporous structure was coated on the surface in the heat source's direction to promote a boiling heat transfer inside the heat spreader. The thermal management devices are tested with the potential applications consisting of the six heat sources placed vertically. As a result, boiling-driven heat spreaders have proven to be an equivalent thermal management method in applications with multiple heat sources and high heat flux targets. In particular, the heat spreader equipped with dot-type supports can make a temperature difference between junctions within 7.6 °C at 1500 W in case of air cooling. Compared to the result (ΔT = 28 °C @ 1500 W) of the solid copper plate of the same size, this thermal packaging demonstrated improved thermal management performances. In addition, we propose a numerical analysis for a boiling-driven heat spreader. The numerical analysis results can predict multiple heat sources' temperature distribution more accurately rather than assuming a two-phase heat spreader as a solid with high thermal conductivity. This study provides valuable insight into the thermal management and thermal packaging design of power electronic devices. It represents a breakthrough in resolving the reliability problem of thermal packaging technology and temperature non-uniformity.
Keywords: Air cooling; Boiling-driven heat spreader; Electronics cooling; Heat sources; Heat spreaders; Multiple heat sources; Power-electronics; Thermal; Thermal management devices; Thermal packaging; Boiling-driven heat spreader; Electronics cooling; Power electronics; Thermal management; Thermal packaging